The immunoglobulin‐like domain of neuregulins potentiates ErbB3/HER3 activation and cellular proliferation. Issue 7 (14th May 2018) - Centa, Ariana; Rodríguez‐Barrueco, Ruth; Montero, Juan Carlos; Pandiella, Atanasio
Abstract : The neuregulins (NRGs) represent a large family of membrane‐anchored growth factors, whose deregulation may contribute to the pathogenesis of several tumors. In fact, targeting of NRG‐activated pathways has demonstrated clinical benefit. To improve the efficacy of anti‐NRG therapies, it is essential to gain insights into the regions of NRGs that favor their pro‐oncogenic properties. Here, we have addressed the protumorigenic impact of different NRG domains. To do this, deletion mutants affecting different NRG domains were expressed in 293 and MCF7 cells. Of the five forms studied, only the wild‐type and a mutant lacking the Ig‐like domain (NRG ΔIg ) were properly sorted to the plasma membrane. Both forms were released as soluble forms to the culture media. However, the mutant NRG ΔIg failed to efficiently activate HER2 and HER3 receptors, signaling pathways, and cell proliferation when compared to wild‐type NRG. Treatment with trastuzumab, a humanized antibody used in the breast cancer clinic, inhibited the constitutive activation of HER2, HER3, and downstream signaling in MCF7 cells constitutively expressing wild‐type NRG. In contrast, this treatment had a marginal effect on MCF7‐NRG ΔIg cells. This study demonstrates that the Ig‐like region of NRGs exerts an important role in their capability to activate ErbB/HER receptors and mitogenic responses. Strategies aimed at targeting NRGs should consider that fact to improve neutralization of the pro‐oncogenic properties of NRGs. Abstract : Ig‐like region of neuregulins (NRGs) is important in their capability to activate ErbB/HER receptors and mitogenic responses. A mutant lacking the Ig‐like domain fails to efficiently activate HER receptors, signaling pathways, and cell proliferation when compared to wild‐type NRG. Strategies aimed at targeting NRGs should consider that fact to improve neutralization of their pro‐oncogenic properties.